2009
DOI: 10.1016/j.envint.2009.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of polybrominated diphenyl ethers (PBDEs) in matched samples of human milk, dust and indoor air

Abstract: Polybrominated diphenyl ethers (PBDEs) are lipophilic, persistent pollutants found worldwide in environmental and human samples. Exposure pathways for PBDEs remain unclear but may include food, air and dust. The aim of this study was to conduct an integrated assessment of PBDE exposure and human body burden using 10 matched samples of human milk, indoor air and dust collected in 2007-2008 in Brisbane, Australia. In addition, temporal analysis was investigated comparing the results of the current study with PBD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
68
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(90 citation statements)
references
References 39 publications
17
68
5
Order By: Relevance
“…Six such studies exist for PBDEs (11,54,(95)(96)(97)(98) with one examining HBCDs (21). With two possible exceptions (96,97), study power is limited by small participant numbers.…”
Section: Sources Of Variability In Concentrationsmentioning
confidence: 99%
“…Six such studies exist for PBDEs (11,54,(95)(96)(97)(98) with one examining HBCDs (21). With two possible exceptions (96,97), study power is limited by small participant numbers.…”
Section: Sources Of Variability In Concentrationsmentioning
confidence: 99%
“…In fact, several groups have performed studies on the exposure routes and the body burden of PBDEs (Johnson et al, 2010;Karlsson et al, 2007;Toms et al, 2009;Wu et al, 2007), and positive correlations were found between PBDEs concentrations in blood/milk and dust. Recently, the U.S. EPA also initiated an exposure assessment of PBDEs and suggested that contact with house dust accounts for between 80 and 90% of total exposures, with the remainder due primarily to food ingestion (U.S. Environmental Protection Agency, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The estimated ÎŁPBDE daily intake from dust for children (49.3 ng/kg b.w./day) during the period from 1-5 years old is six time higher than for adults (7.7 ng/kg b.w./day) because of children's lower body weight and higher dust intake (Lorber, 2008). Toms et al (2009) calculates that the ÎŁPBDE daily intake from dust in children ranges between 33 and 118 ng/day but for adults is only from 2.5 to 59 ng/day.…”
Section: -2010mentioning
confidence: 99%
“…A recent study of family members with nonoccupational exposure to PBDEs suggests that toddlers and children have a higher risk of PBDE exposure and face higher risks of PBDE-related health effects than their parents (Fischer et al, 2006). Toms et al (2009) investigates concentrations of PBDEs in matched samples of breast milk, dust, and indoor air to determine if levels are based on congener profiles, as the level of bromination increased the contribution of intake decreased via breast milk and increased via dust and the contribution of inhalation to total PBDE intake was minor. The estimated ÎŁPBDE daily intake from dust for children (49.3 ng/kg b.w./day) during the period from 1-5 years old is six time higher than for adults (7.7 ng/kg b.w./day) because of children's lower body weight and higher dust intake (Lorber, 2008).…”
Section: -2010mentioning
confidence: 99%